Refer to the diagram shown below.
We want to find y in terms of d, φ and θ.
By definition,
[tex]tan (\theta) = \frac{y}{x} \\\\ tan( \phi) = \frac{y}{x-d} [/tex]
Therefore
y = x tan(θ) (1)
y = (x - d) tan(φ) (2)
Equate (1) and (2).
[tex](x - d) \, tan(\phi) = x \, tan(\theta) \\ x[tan(\phi) - tan(\theta)] = d \, tan(\phi) \\ x= \frac{d tan(\phi)}{tan(\phi)-tan(\theta)} [/tex]
From (1), obtain the required expression for y.
Answer:
[tex]y= \frac{d \, tan(\phi) \, tan(\theta)}{tan(\phi)-tan(\theta)} [/tex]